2015
DOI: 10.5152/turkpediatriars.2015.2620
|View full text |Cite
|
Sign up to set email alerts
|

Is there any difference between high-risk infants with different birth weight and gestational age in neurodevelopmental characters?

Abstract: Aim: This study is aimed to investigate differences between cognitive, language and motor development of high-risk infants related to birth weight and gestational age. Material and Methods:One hundred sixty high-risk infants who were born 32 weeks, 1 500 gr and below included in this study. According to corrected age, 58 infants were 1 month, 72 were at 4 months, 82 were at 8 months and 65 were 12 months old. Infants were seperated two groups according to gestational age <30 weeks and 30-32 weeks and birth wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Some studies have reported that infants born premature present significantly lower scores on language tests compared with those of children born full term (2,4,9,13,18,20,22,24) and that there is correlation between GA and birth weight and altered language development (2,4,9) . A study did not find differences in the performance of infants born preterm and full term regarding language, cognition, and motor development (12) . It is worth noting that the studies that addressed the development of language skills in preterm infants emphasized that although delay in language development is a frequent condition, variability is observed even in the absence of deficiencies and interference of socioeconomic status (12,14,28) .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies have reported that infants born premature present significantly lower scores on language tests compared with those of children born full term (2,4,9,13,18,20,22,24) and that there is correlation between GA and birth weight and altered language development (2,4,9) . A study did not find differences in the performance of infants born preterm and full term regarding language, cognition, and motor development (12) . It is worth noting that the studies that addressed the development of language skills in preterm infants emphasized that although delay in language development is a frequent condition, variability is observed even in the absence of deficiencies and interference of socioeconomic status (12,14,28) .…”
Section: Discussionmentioning
confidence: 92%
“…A study did not find differences in the performance of infants born preterm and full term regarding language, cognition, and motor development (12) . It is worth noting that the studies that addressed the development of language skills in preterm infants emphasized that although delay in language development is a frequent condition, variability is observed even in the absence of deficiencies and interference of socioeconomic status (12,14,28) . Individuals born preterm with LBW and VLBW, despite the high probability of changes in development, do not constitute a homogeneous group.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The motor development of preterm infants and very low weight and also the results of studies on motor and cognitive development of such children indicate that premature infants appear to be physically normal, but they have significantly lower motor functional and cognitive performance than their peers [9][10][11]. However, some results showed that there was no difference in motor function between the premature children and normal children [12,13]. Therefore assessment of motor domain is not only for understanding and to promote the aspects of development but also to understand the possible delay and improve the instrument in this domain [14].…”
Section: Introductionmentioning
confidence: 99%
“…intercorrências maternas ou perinatais, dentre outras (PÁEZ-PINEDA; VALENCIA-VALENCIA; ORTIZ-CALDERON, 2014;COELHO et al, 2016;IONIO et al, 2016;MELLO et al, 2016;ZAMBRANA et al, 2016;ADHIKARI;RAO, 2017;GASPARINI et al, 2017;MILNER et al, 2017;SANCHES-JOYA et al, 2017;KILLEEN et al, 2017). Alguns estudos tiveram na sua casuística prematuros nascidos abaixo de 32 semanas de IG, ou seja, a casuística era composta por prematuro extremos e acentuados, associados ou não a outras variáveis (KARA et al, 2015;LINSELL et al, 2015;VELIKOS et al, 2015;WONG et al, 2016); outros, com crianças nascidas abaixo de 35 semanas de IG e baixo peso (MAGALHÃES et al, 2011) KARA et al, 2015;BENASSI et al, 2016;PAREKH et al, 2016;RIBEIRO et al, 2016;PÉRES-PEREIRA et al, 2016;TAYLOR;CLARCK, 2016;ZAMBRANA et al, 2016;JOHNSON et al, 2017;KILLEEN et al, 2017;GASPARINI et al, 2017;PUTNICK et al, 2017;SANCHES-JOYA et al, 2017;SYNNES et al, 2017;YAARI et al, 2017), com a utilização de vários instrumentos voltados para este fim. (PACHELLI, 2015;RIBEIRO et al, 2017).…”
Section:  Independent Samples Testunclassified